AT(2) receptor-dependent vasodilation is mediated by activation of vascular kinin generation under flow conditions - Katada, Jun (2002)
1. Physiological roles of angiotensin II type 2 receptor (AT(2)) are not well defined. This study was designed to investigate the mechanisms of AT(2)-dependent vascular relaxation by studying vasodilation in pressurized and perfused rat mesenteric arterial segments. 2. Perfusion of angiotensin II in the presence of AT(1) antagonist elicited vascular relaxation, which was completely dependent on AT(2) receptors on endothelium. FR173657 (>1 μM), a bradykinin (BK) B(2)-specific antagonist, significantly suppressed AT(2)-dependent vasodilation (maximum inhibition: 68.5% at 10 μM). 3. Kininogen-deficient Brown Norway Katholiek rats showed a significant reduction in AT(2)-mediated vasodilatory response compared with normal wild-type Brown Norway rats. 4. Indomethacin (>1 μM), aprotinin (10 μM) and soybean trypsin inhibitor (10 μM) also reduced AT(2)-dependent vasodilation. 5. Our results demonstrated that stimulation of AT(2) receptors caused a significant vasodilation through local production of BK in resistant arteries of rat mesentery in a flow-dependent manner. Such vasodilation counterbalances AT(1)-dependent vasoconstriction to regulate the vascular tone.